The Potential of Blockchain to Increase the Effectiveness of Management Accounting: A Systematic Literature Review - Mahdani, Rimal; Putri, Cut Widya Aulia; Risnafitri, Hafizhah (Indatu Journal of Management and Accounting, 2023)
This comprehensive literature review examines how blockchain technology may enhance management accounting procedures. The investigation indicates that blockchain technology might change financial data administration and transmission, improving precision, effectiveness, and dependability. However, scalability, interoperability, and data protection must be addressed. The review also underlines the need for greater research to fully understand how blockchain technology affects management accounting in ever-changing organizational contexts. Empirical studies examine blockchain technology's actual applications, whereas conceptual studies examine theoretical frameworks and models. Integrating blockchain technology with Artificial intelligence (AI) and eXtensible Business Reporting Language (XBRL) enhances its use in accounting systems. The study shows that blockchain technology might alter management accounting operations, improving financial data quality and dependability for decision-making. Electronic procurement, when integrated with Enterprise Resource Planning (ERP) and Accounting Information Systems (AIS), can improve transparency, efficiency, and operational automation. This report suggests additional research, adoption strategies, training methodologies, data privacy concerns, and ongoing monitoring.